Efektivitas Teknik Lamaze Breathing terhadap Peningkatan Kualitas Kontraksi Uterus pada Ibu Bersalin Primigravida Kala I Fase Aktif - Solichatin; Retno Pudiyaningtiyas (Rena Cipta Mandiri, 2025)
Childbirth is a natural process experienced by pregnant women to give birth to a full-term baby followed by the birth of the placenta and fetal membranes from the mother's uterus. Prolonged labor is caused by many factors, one of which is caused by inadequate uterine contractions. One effective method in dealing with uterine contractions is the lamaze breathing technique. The objective of this study was to determine whether the lamaze breathing technique is effective against uterine contractions in the first stage of labor in the active phase of primigravida. This research method uses a quasi experimental with a one group pretest-posttest design. The research sample was primigravida in the first stage of the active phase at walisongo 1 gresik hospital who met the inclusion criteria of 36 mothers giving birth. The measuring instrument used in this study was a partograph. The independent variable was the lamaze breathing technique while the dependent variable was uterine contractions in the first stage of labor in the active phase. The results of the wilcoxon signed-rank Test analysis P Value = 0.001 <α (0.05) so it can be concluded that the Lamaze Breathing Technique is effective against uterine contractions in the first stage of labor in the active phase. This method is expected to be applied in health facilities from the lower level (Midwife Clinic) to the upper level (Hospital) and can provide effective options and ensure safety for both mothers and babies being born.